Isolation and characterisation of lactobacilli from the female anogenital tract in healthy Malaysian women and its probiotics potential - Choo, Sulin (2017)
The female urogenital tract has long been recognised as a reservoir for a great diversity of microorganisms. The most prominent species isolated from this anatomical site among healthy women has been identified as lactobacilli. Previous studies conducted on these species indicate that they function to maintain a healthy reproductive system and protect the host from harm. In this study, the characteristics and properties of several lactobacilli strains isolated from the urogenital tract and perianal region of healthy female participants were evaluated to identify potential probiotic strains. The lactobacilli strains were isolated from twenty out of fifty-two Malaysian women wherein a total of sixty-two species of lactobacilli were identified using 16S rDNA sequencing. The most common species isolated in the present study were identified as L. reuteri (n = 14), L. mucosae (n = 12), L. fermentum (n = 10) and L. oris (n = 9). The least common species were L. vaginalis (n = 5), L. gasseri (n = 4), L. delbrueckii (n = 3), L. jensenii (n = 2) followed by L. salivarius, L. plantarum and L. rhamnosus (all with n = 1 isolate each). All lactobacilli strains demonstrated the ability to reduce the growth of several reference and clinical strains of Candida albicans and Candida glabrata, as observed in the broth microdilution assay. Five of the lactobacilli strains with potent anti-Candida effects were selected for subsequent assays based on the characteristics exhibited. These five lactobacilli strains exhibited fairly strong antimicrobial effects against ten of the pathogens tested as observed from the agar plug diffusion assay. All five lactobacilli strains could produce varying degrees of hydrogen peroxide, H2O2 as evaluated using 3’3, 5’5 tetramethylbenzidine (TMB) agar. Meanwhile, the differences in lactic acid production among the five strains indicate that the growth inhibitory mechanisms may differ for each strain. Besides that, the findings from the autoaggregation and coaggregation assays indicate that these strains have a high percentage of autoaggregation (50 – 80%) among themselves and coaggregation abilities with the fungal pathogens (75 – 90%). Only one of the lactobacilli strains, Lactobacillus reuteri 29B was also able to withstand highly acidic environment and high concentration of bile for up to four hours as indicated in the pH and bile tolerance test. The five lactobacilli strains isolated showed the ability to tolerate the presence of 10% of nonoxynol-9 (N-9) with no or only a slight reduction in growth for most of the strains. The results obtained from this study indicates that whilst the five strains have promising characteristics, L. reuteri 29B is the ideal strain to be considered as a probiotic. Further studies are required to prove the suitability of L. reuteri 29B as a probiotic.